Green Ocean Strategy for Sustainable Development of Wayang Sasak - Arin Saumi Fortuna; Bambang Suharto; Alya Farras Azzahra; Angelia Setya Lukita; Aflahah Ramadhani Nidia Saputri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Wayang Sasak, a traditional puppet theater from Lombok, Indonesia, represents a significant element of cultural heritage imbued with profound historical and spiritual values. However, the current cultural landscape shows a decline in its relevance due to the challenges posed by globalization and the lack of innovative preservation strategies. This study aims to address these issues by analyzing the implementation of the Green Ocean Strategy, which integrates cultural preservation with environmental sustainability and creative innovation. Using a Systematic Literature Review (SLR) approach, this research critically examines 50 peer-reviewed studies, ensuring a rigorous selection process that accounts for relevance, methodological robustness, and empirical findings. The analysis focuses on cultural preservation, sustainable creative industries, and innovation strategies to identify both opportunities and challenges for Wayang Sasak’s development. Key statistical measures, including effect sizes and significance levels, have been incorporated to enhance the validity of the findings. The results indicate that while Wayang Sasak has immense potential as a sustainable creative industry product, it faces key obstacles such as limited access to technology and eco-friendly materials. However, the study highlights specific significant opportunities, particularly the percentage of analyzed studies supporting digital integration and the economic indicators suggesting viability. Furthermore, collaborative efforts with the tourism and creative sectors in Lombok offer promising pathways for enhancing the economic viability and international appeal of Wayang Sasak. The conclusion emphasizes the strategic importance of adopting the Green Ocean Strategy to ensure the sustainable development of this cultural heritage. Practical implications for stakeholders include actionable recommendations to strengthen community engagement, innovate production methods, and align with global sustainability trends. By adopting adaptive strategies, Wayang Sasak can thrive as a vital component of the creative economy while preserving its traditional essence